PENGATURAN HUKUM PENANGANAN ILLEGAL FISHING DI WILAYAH YURIDIKSI INDONESIA - Herdiman, Herdiman; Sidarta, Dudi Djaja; Cornelis, Vieta Imelda; Soekorini, Noenik; Mannulusi, Andik (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This research analyzes the national legal policy in dealing with illegal fishing in Indonesian jurisdiction, particularly through the sinking of perpetrator vessels in accordance with the perspective of national and conventional law. Illegal fishing is an offense that not only harms the country's economy but also has a significant impact on the marine ecosystem. This research uses a descriptive-qualitative method with a normative legal approach to evaluate the effectiveness of the Ministry of Maritime Affairs and Fisheries' (MMAF) ship sinking policy. The results show that this policy, although controversial, has a strong legal basis, both in the Fisheries Law and the 1982 Convention on the Law of the Sea (UNCLOS). In addition, this policy is proven to reduce the number of illegal fishing cases in a certain period. This research also highlights the importance of preventive efforts and international diplomacy in reducing cross-border violations, so that this policy can run more effectively and sustainably. Strict law enforcement but still respecting the principle of justice is the main key to protecting Indonesia's marine resources. Keywords : Illegal Fishing, Ocean Sovereignty, Legal Policy, UNCLOS, Ship Sinking